Molecular cloning of the spo0B sporulation locus in bacteriophage lambda. - Ferrari, F A (1982)
The stage 0 sporulation locus spo0B has been mapped by transformation between the pheA and spoIVF loci. Analysis of the behavior of alleles of the spo0B locus in trpE26 merodiploid strains indicates that all of the known alleles of this locus comprise a single complementation group. The spoIVF88 mutation was found to reside in a separate complementation group. The chromosomal region surrounding and including the spo0B locus was cloned in the lambda vector Charon 4A. Extensive restriction endonuclease analyses of the inserts in these phage revealed that an EcoRI fragment of DNA of 2.3 kilobases had transforming activity for spo0B mutations. Examination of the physical and genetic maps of the locus suggested that the entire spo0B locus is contained within this fragment. Subcloning of restriction endonuclease fragments of the lambda inserts and transformation analyses allowed assignment of surrounding genetic loci to specific DNA fragments.